Endothelial Stromal PD-L1 (Programmed Death Ligand 1) Modulates CD8+ T-Cell Infiltration After Heart Transplantation. (24th September 2021) - Bracamonte-Baran, William; Gilotra, Nisha A.; Won, Taejoon; Rodriguez, Katrina M.; Talor, Monica V.; Oh, Byoung C.; Griffin, Jan; Wittstein, Ilan; Sharma, Kavita; Skinner, John; Johns, Roger A.; Russell, Stuart D.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The role of checkpoint axes in transplantation has been partially addressed in animal models but not in humans. Occurrence of fulminant myocarditis with allorejection-like immunologic features in patients under anti-PD1 (programmed death cell protein 1) treatment suggests a key role of the PD1/PD-L1 (programmed death ligand 1) axis in cardiac immune homeostasis. Methods: We cross-sectionally studied 23 heart transplant patients undergoing surveillance endomyocardial biopsy. Endomyocardial tissue and peripheral blood mononuclear cells were analyzed by flow cytometry. Multivariate logistic regression analyses including demographic, clinical, and hemodynamic parameters were performed. Murine models were used to evaluate the impact of PD-L1 endothelial graft expression in allorejection. Results: We found that myeloid cells dominate the composition of the graft leukocyte compartment in most patients, with variable T-cell frequencies. The CD (cluster of differentiation) 4:CD8 T-cell ratios were between 0 and 1.5. The proportion of PD-L1 expressing cells in graft endothelial cells, fibroblasts, and myeloid leukocytes ranged from negligible up to 60%. We found a significant inverse logarithmic correlation between the proportion of PD-L1 + HLA (human leukocyte antigen)-DR + endothelial cells and CD8 + T cells (slope, −18.3 [95% CI, −35.3 to −1.3]; P =0.030). PD-L1 expression and leukocyte patterns were independent of demographic, clinical, and hemodynamic parameters. We confirmed the importance of endothelial PD-L1 expression in a murine allogeneic heart transplantation model, in which Tie2 Cre pdl1 fl/fl grafts lacking PD-L1 in endothelial cells were rejected significantly faster than controls. Conclusions: Loss of graft endothelial PD-L1 expression may play a role in regulating CD8 + T-cell infiltration in human heart transplantation. Murine model results suggest that loss of graft endothelial PD-L1 may facilitate alloresponses and rejection.